2020
DOI: 10.33474/jimmu.v4i2.2732
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Model Diamond Porter Dalam Membangun Keunggulan Bersaing Pada Kawasan Agrowisata Kebun Belimbing Ngringinrejo Bojonegoro

Abstract: This study aims to examine the competitive advantage analysis through the Porter’s diamond model in Agrotourism Ngringinrejo Bojonegoro. The research method used is descriptive with qualitative approach. Data collection techniques are done by interview, observation and documentation. The results showed important determinant in the competitive advantage of Agrotourism Ngringinrejo Bojonegoro, in accordance with the diamond porter model, consist of factor conditions; demand conditions; firms structure, strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
0
0
4
Order By: Relevance
“…The determination of tourist village clusters in Jepara Regency based on the Porter diamond model is in line with research conducted by Saraswati et al (2019) for building a competitive advantage in the Ngringingrejo Bojonegoro starfruit agrotourism area. This showed that the important determinant of competitive advantage there is in line with the model.…”
Section: Resultssupporting
confidence: 73%
“…The determination of tourist village clusters in Jepara Regency based on the Porter diamond model is in line with research conducted by Saraswati et al (2019) for building a competitive advantage in the Ngringingrejo Bojonegoro starfruit agrotourism area. This showed that the important determinant of competitive advantage there is in line with the model.…”
Section: Resultssupporting
confidence: 73%
“…Upaya dalam pengembangan suatu destinasi wisata akan lebih mudah jika para stakeholders mampu secara tepat dalam proses identifikasi potensi yang menjadi daya tarik suatu destinasi serta mengetahui dan memahami motivasi para wisatawan (Saraswati, E., Hatneny, A. I., & Dewi, 2020). Paradigma pengembangan baru harus dikembangkan dalam pengelolaan destinasi guna memaksimalkan pencapaian pengembangan industri pariwisata, industri ini harus mampu menghasilkan keuntungan berkelanjutan, artinya keuntungan harus didapat saat ini maupun dimasa yang akan datang (Saraswati dkk 2019:110).…”
Section: Pendahuluanunclassified
“…Hal ini dikarenakan kurangnya inovasi pengembangan produk susu sapi menjadi olahan baru, kebanyakan para pelaku UMKM hanya menjual susu sapi secara murni tanpa mengolahnya menjadi olahan baru sehingga nilai jualnya masih rendah. Apabila pelaku usaha mampu berinovasi untuk mengolah susu menjadi produk baru maka nilai jualnya pun menjadi tinggi, dan dapat memberikan keuntungan berkelanjutan, artinya keuntungan yang diperoleh dapat diterima pada saat ini maupun pada waktu yang akan datang (Saraswati, E., Hatneny, A. I., & Dewi, 2020) Harga jual susu murni di pasaran hanya mencapai Rp 8.000,-untuk satu liternya, sedangkan harga jual susu yang diolah menjadi susu kemasan atau minuman susu berperisa mancapai kisaran Rp 20.000,-per liternya. Masih banyaknya pelaku UMKM susu sapi yang hanya menjual produk berupa susu murni yang bernilai jual murah tentu belum mampu mengingkatkan perekonomian pelaku usaha secara optimal karena perolehan laba yang sedikit.…”
Section: Pendahuluanunclassified